The Impossible Observer : Reason and the Reader in Eighteenth-Century Prose - Uphaus, Robert W. (Book collections on Project MUSE., 1979)
Rationality, objectivity, symmetry: were these really principles urged and exemplified by eighteenth-century English prose? In this persuasive study, Robert W. Uphaus argues that, on the contrary, many of the most important works of the period do not actually lead the reader into a new awareness of just how problematical, how unsusceptible to reason, both the world and our easy assumptions about it are. Uphaus discusses a broad range of writers -- Swift, Defoe, Mandeyville, Richardson, Fielding, Sterne, Johnson, and Godwin -- showing that beneath their variety lies a fundamentally similar chall.